Designing T cells for Cancer Immunotherapy - Huye, Leslie E. (2010)
Adoptive transfer of T cells can enhance immune-mediated elimination of tumor cells and provides a specific, non-toxic cancer therapy. This approach has been effective in treating some hematologic and solid malignancies. In addition, the ability to genetically modify T cells to enhance their activity and persistence as well as overcome tumor immune evasion mechanisms has the potential to increase the success of these therapies in a wide range of tumors. In this review we discuss methods for gene transfer and specific modifications that have been made to T cells.